Transformasi Perpustakaan Khusus menjadi Data Labs dalam Mendukung Open Data dan Open Government di Indonesia - Madiareni Sulaiman (Perpustakaan Nasional, 2021)
Data Labs is one of the elements of the data center and has been owned by almost all organizations in the special library environment for government and private institutions, on behalf of the data and information center. The term, data labs, become the focus of the study in its function to maximize the use of data (reusable data) in institutional repositories and generally managed by special libraries. The discussion focuses on material that answers the function/role of a special library as data labs; current and future challenges; how information professionals respond to these challenges; as well as how to see the potential of the collections and content they have. Survey analysis and data collection through depth-interviews are a form of research approach in this study. Based on the results of the study, it was found that most of the respondents had played a part in supporting the openness of data in their institutions, and had some of the functions of data labs. There are several things that need to be considered further, namely the points for the roles they have (digital divide, data management, and knowledge workers), challenge points (policies and data openness ecosystem), response points (targeted-groups, business processes, action plans, and skill-upgrade), as well as points for the potential collections and content owned by the institutions (advocacy, needs analysis, open data principles, and inclusiveness). The research results are expected to be the basis for policy in determining the position of special libraries with data labs functions to support institutions’ performance. So it can be concluded that in supporting the transformation of this function, it is necessary to provide competent employees in accordance with the needs for the future development of data repository content, as well as in line with government programs and the global community related to data transparency and governance in Indonesia.